From indoors to outdoors: Impact of waste anesthetic gases on occupationally exposed professionals and related environmental hazards – A narrative review and update - Silva, Mariane A.P. [UNESP]; Carvalho, Lorena I.M.; Destro, Maria Vitória [UNESP]; Braz, Leandro Gobbo [UNESP]; Braz, Mariana Gobbo [UNESP] (Elsevier, 2025)
Waste anesthetic gases (WAGs) are trace-concentration inhaled anesthetics that exist worldwide because they are released into the ambient air of operating rooms (ORs) and post-anesthesia care units. WAGs cause indoor contamination, especially in ORs lacking proper scavenging systems, and occupational exposure, while promoting climate change through greenhouse gas/ozone-depleting effects. Despite these controversial features, WAGs continue to pose occupational health hazards. Occupational exposure to WAGs has been linked to oxidative stress and cytotoxic, genotoxic and mutagenic potential. This review aims to analyze and update the literature on WAG monitoring, the impact of WAGs on occupationally exposed personnel and their effect on the environment. The awareness of exposed professionals in human and veterinary medicine is crucial. The implementation of biomonitoring practices and WAG occupational exposure limiting policies is needed. Promoting a sustainable healthcare system is also important for mitigating the impact of WAGs on global warming.
Keywords: Greenhouse gases; Inhalation anesthetics; Monitoring; Occupational exposure; Toxic potential